Effect of Storage Temperature and Oil Palm Leaf Ethanol Extract (OPLEE) on Shelf Life of PKO and VCO Body Lotion - Hasgita Hasgita; Arya Wiranata; Jechonias Mongarisson; Dina Mardhatilah (Universitas Islam Raden Rahmat, Malang, 2026)
Body lotions based on Palm Kernel Oil (PKO) and Virgin Coconut Oil (VCO) are susceptible to oxidation which can cause tarnishness, changes in smell and color, as well as decreased physical and chemical stability of the product. The addition of natural antioxidants such as oil palm leaf ethanol extract (OPLEE) is one of the efforts to increase this stability. This study used a two-factor design, namely OPLEE concentration (1.5%; 2%; 2.5%) and storage temperature (4°C, 25°C, 40°C) for 35 days. The results showed that the preparations remained homogeneous at 4°C and 25°C, but experienced phase separation at 40°C from day 28. The pH value tends to increase during storage with the best stability at the C treatment with the lowest slope of 0.0191-0.0371. Antioxidant activity decreased, with treatment B showing the best stability at the lowest slope value of 0.1646-0.8123, while the peroxide value increased with the increase in temperature with the lowest slope value at high temperature of 0.0971. The results of ANOVA's Repeated Measures analysis showed that the pH, antioxidant activity, and peroxide value changed significantly (p<0.05), while the physical parameters were relatively stable. Overall, the low storage temperature (4°C) and OPLEE concentration of 2.5% (B) provide the best stability in maintaining the quality of the body lotion during storage. Therefore, OPLEE as a natural antioxidant in cosmetic formulations can be an alternative active ingredient that supports the development of more stable and value-added body lotion products.